2008
DOI: 10.2174/1874123100802010066
|View full text |Cite
|
Sign up to set email alerts
|

New Metalized Polyimide Films Structure and Physical Properties

Abstract: Abstract:The classical techniques of PI film metallization by either vapour deposition or electrochemical reduction of metals involve necessary technological steps such as polymer surface modification via plasma or ion beam, electron beam, or photolytic treatment, or surface sensitization by the conferment of catalytic properties, in order to enhance metal-PI adhesion, which is the main problem to be overcome in all processes.The technology presented differs by the use of another chemical approach yielding ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The available reports mainly deal with commercial structures (Kapton) and highlight fundamental aspects regarding the mechanism of the metallization process, effect of the electron irradiation on thermal conduction of metalized PI, describe certain techniques of PI film metallization, while indicate the practical use as filters for X-Ray astronomy, circuit boards using TAB (tape automated bonding), magnetic tape and space applications. [26][27][28][29][30][31][32] For example, Ramos [33] performed a theoretical study on bonding strength of metal/Kapton commercial PI interface. By means of self-consistent molecular dynamics, it was shown that despite the low charge transfer between PI and selected metals (Cu, Ni, Cr), the bond formation generates charge rearrangement along the polymer atoms away from the reaction site.…”
mentioning
confidence: 99%
“…The available reports mainly deal with commercial structures (Kapton) and highlight fundamental aspects regarding the mechanism of the metallization process, effect of the electron irradiation on thermal conduction of metalized PI, describe certain techniques of PI film metallization, while indicate the practical use as filters for X-Ray astronomy, circuit boards using TAB (tape automated bonding), magnetic tape and space applications. [26][27][28][29][30][31][32] For example, Ramos [33] performed a theoretical study on bonding strength of metal/Kapton commercial PI interface. By means of self-consistent molecular dynamics, it was shown that despite the low charge transfer between PI and selected metals (Cu, Ni, Cr), the bond formation generates charge rearrangement along the polymer atoms away from the reaction site.…”
mentioning
confidence: 99%